Retinal Photography Without Mydriatics - Alloucherie, Yves J (Canadian Journal of Optometry, 1982)
Two main reasons may be given to explain why retinal photography is not used more frequently by optometrists: the high cost of the specialized cameras required and the "need" for mydriasis. It is of course true that fundus cameras, like all other complex optical instruments, are expensive. It will however be shown in this paper that very acceptable photographs of the retina may often be obtained easily, even by inexperienced optometry students, without any drug-induced mydriasis, after only a few minutes of instruction and experience.